2021
DOI: 10.1007/s12035-021-02373-2
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin3F Drives Dendritic Spine Pruning Through Rho-GTPase Signaling

Abstract: Dendritic spines of cortical pyramidal neurons are initially overproduced then remodeled substantially in the adolescent brain to achieve appropriate excitatory balance in mature circuits. Here we investigated the molecular mechanism of developmental spine pruning by Semaphorin 3F (Sema3F) and its holoreceptor complex, which consists of immunoglobulin-class adhesion molecule NrCAM, Neuropilin-2 (Npn2), and PlexinA3 (PlexA3) signaling subunits. Structure-function studies of the NrCAM-Npn2 interface showed that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 78 publications
0
14
0
1
Order By: Relevance
“…Spine addition and elimination is related to net gain and loss of excitatory synapses over lifetime and is influenced by factors like PSD recruitment, sensory stimulation etc., [ 33 ]. Semaphorin 3F-induced activation of Tiam 1-Rac1-3-LIMK1/2-Cofilin1 and RhoA-ROCK1/2-Myosin II in dendritic spines regulates pruning of spines [ 34 ].…”
Section: Dendritic Spines Biosynthesismentioning
confidence: 99%
“…Spine addition and elimination is related to net gain and loss of excitatory synapses over lifetime and is influenced by factors like PSD recruitment, sensory stimulation etc., [ 33 ]. Semaphorin 3F-induced activation of Tiam 1-Rac1-3-LIMK1/2-Cofilin1 and RhoA-ROCK1/2-Myosin II in dendritic spines regulates pruning of spines [ 34 ].…”
Section: Dendritic Spines Biosynthesismentioning
confidence: 99%
“…Intriguingly, a recent study showed that neuropilin 2 (Nrp2), an axon guidance molecule, plays crucial roles in instructing circuit formation from the MOB to MeA for the transmission of attractive social signals in the brain ( Inokuchi et al., 2017 ). Given that the role of both neuropilin 1 (Nrp1) and its ligand Sema-3A in axon guidance processes toward the MOB depends on functional ciliary AC3-mediated cAMP signaling in the MOE ( Col et al., 2007 ; Henion et al., 2011 ; Imai et al., 2009 ; Schwarting and Henion, 2011 ) and is associated with cilium-related Hedgehog signaling ( Cai et al., 2021 ; Hillman et al., 2011 ; Pinskey et al., 2017 ) and that the ablation of neuropilin and its ligand in mice leads to pleiotropic phenotypes ( Assous et al., 2019 ; Cariboni et al., 2007 ; Demyanenko et al., 2014 ; Duncan et al., 2021 ; Li et al., 2019 ; Maden et al., 2012 ; Mohan et al., 2018 , 2019 ; Riccomagno et al., 2012 ; Tan et al., 2019 ; Tran et al., 2009 ; van der Klaauw et al., 2019 ; Vanacker et al., 2020 ) that mirror the functions of AC3 in multiple brain areas, we hypothesize that the pleiotropic phenotypes illustrated in these AC3-deficient mice, including the defects in infanticidal behaviors observed in this study, might be caused by cilia-associated neuropilin signaling in a brain region-specific and cell type-specific manner. Collectively, the results indicate that similar to other ciliopathy-associated proteins, AC3 could be reasonably identified as a key player in associated ciliopathies, although why and how unique ciliary AC3-mediated cAMP signaling plays multiple functions across different brain areas and neuronal subtypes, including the infanticidal behaviors involved in the MOE, AON, and VMH regions, remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Given its reversibility, palmitoylation could give rise to bidirectional transformation between a palmitoylated state and a non-palmitoylated state that takes part in disulfide-linked dimer formation. In addition, given the critical role of neuron-glial related cell adhesion molecule (NrCAM) in Sema3F-dependent dendritic spine pruning in cortical neurons (Demyanenko et al, 2014; Duncan et al, 2021), it will be of interest to investigate the role of Nrp-2 palmitoylation in the physical and functional interactions between the Nrp-2/PlexA3 holoreceptor complex and NrCAM.…”
Section: Discussionmentioning
confidence: 99%
“…Sema3F and Sema3A bind distinct holoreceptor complexes that include neuropilin (Nrp) and plexin (Plex) transmembrane proteins; Sema3F exerts many of its effects via a holoreceptor complex that includes Nrp-2/PlexA3, whereas Sema3A acts through a holoreceptor complex that includes Nrp-1/PlexA4 (Yaron et al, 2005). Recent work provides insight into the signaling pathways that mediate Sema3F/Nrp-2-dependent cytoskeletal rearrangements resulting in dendritic spine pruning in cortical neurons, including contributions by specific immunoglobin superfamily transmembrane proteins that mediate select responses to secreted semaphorins and proteins that regulate actin cytoskeleton dynamics (Demyanenko et al, 2014; Duncan et al, 2021). However, molecular mechanisms that regulate neuropilin subcellular localization and underlie divergent Sema3F and Sema3A functions in cortical neurons remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%